Community Participation in Health Systems Research: A Systematic Review Assessing the State of Research, the Nature of Interventions Involved and the Features of Engagement with Communities. - Asha S George; Vrinda Mehra; Kerry Scott; Veena Sriram (PLoS ONE, 2015)
Background Community participation is a major principle of people centered health systems, with considerable research highlighting its intrinsic value and strategic importance. Existing reviews largely focus on the effectiveness of community participation with less attention to how community participation is supported in health systems intervention research. Objective To explore the extent, nature and quality of community participation in health systems intervention research in low- and middle-income countries. Methodology We searched for peer-reviewed, English language literature published between January 2000 and May 2012 through four electronic databases. Search terms combined the concepts of community, capability/participation, health systems research and low- and middle-income countries. The initial search yielded 3,092 articles, of which 260 articles with more than nominal community participation were identified and included. We further excluded 104 articles due to lower levels of community participation across the research cycle and poor description of the process of community participation. Out of the remaining 160 articles with rich community participation, we further examined 64 articles focused on service delivery and governance within health systems research. Results Most articles were led by authors in high income countries and many did not consistently list critical aspects of study quality. Articles were most likely to describe community participation in health promotion interventions (78%, 202/260), even though they were less participatory than other health systems areas. Community involvement in governance and supply chain management was less common (12%, 30/260 and 9%, 24/260 respectively), but more participatory. Articles cut across all health conditions and varied by scale and duration, with those that were implemented at national scale or over more than five years being mainstreamed by government. Most articles detailed improvements in service availability, accessibility and acceptability, with fewer efforts focused on quality, and few designs able to measure impact on health outcomes. With regards to participation, most articles supported community's in implementing interventions (95%, n = 247/260), in contrast to involving communities in identifying and defining problems (18%, n = 46/260). Many articles did not discuss who in communities participated, with just over a half of the articles disaggregating any information by sex. Articles were largely under theorized, and only five mentioned power or control. Majority of the articles (57/64) described community participation processes as being collaborative with fewer describing either community mobilization or community empowerment. Intrinsic individual motivations, community-level trust, strong external linkages, and supportive institutional processes facilitated community participation, while lack of training, interest and information, along with weak financial sustainability were challenges. Supportive contextual factors included decentralization reforms and engagement with social movements. Conclusion Despite positive examples, community participation in health systems interventions was variable, with few being truly community directed. Future research should more thoroughly engage with community participation theory, recognize the power relations inherent in community participation, and be more realistic as to how much communities can participate and cognizant of who decides that.